Using websites and social media to support local community stakeholder attendance at project town hall meetings - Anna Lund Jepsen; Pernille Eskerod; Kon Shing Kenneth Chung; Jingbo Zhang; Mauro Ortiz (Project Leadership and Society)
Engaging local community stakeholders in projects is important. A project town hall meeting is a common practice to do so. However, many project town hall meetings suffer from low attendance. This study investigates how the project organization can use its website and social media to support attendance. The study draws on literature on social media marketing, the customer journey concept, and the use of different appeal elements. It applies a case study approach with two cases: The Western Sydney Airport project and the London Heathrow Expansion project. We found that the project organizations used their websites and the social media Facebook, X and YouTube to a limited extent. Furthermore, they mostly used rational and transactional appeals, thus foregoing the chance to engage stakeholders in attending by application of interactional appeals. Based on the findings, we offer a framework for use of own websites and social media to support the stakeholder journey towards attending project town hall meetings. Our research enriches project management knowledge by highlighting what to consider in the application of websites and social media for local community stakeholder engagement.